Differential diagnosis of fasciola hepatica from different animal hosts by pcr - Osman Selcuk Aldemir; Mederle Narcisa (Eurasian Journal of Veterinary Sciences)
Aim: The objective of this study was evaluated differentiational diagnosis of Fasciola hepatica from sheep and goat by PCR. Materials and Methods: F. hepatica were obtained from sheep and goat. These parasites were washed several times with pH:7.4 phosphate-buffered saline and phenol extraction/ ethanol precipitation method was employed in genomic DNA extraction. In order to optimization of the PCR conditions, five primers were selected to amplify the DNA of each F. hepatica. Results: Both sheep and goat were amplified products in different numbers and sizes by RAPD-PCR technique. The results show that different primers gave different bands (fragments) and allowed to identify genetic variations of F. hepatica. These bands were species-specific to F. hepatica from goat and sheep. Conclusions: The RAPD-PCR method can be useful for the differentiational diagnosis of F. hepatica of sheep and goat.